1994
DOI: 10.1007/bf00297199
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of vitamin D induced stone formation by calcium

Abstract: Investigations were carried out as to whether cytoprotective agents such as calcium antagonists can influence vitamin D induced nephrolithiasis. Increased vitamin D levels are found in 10-30% of all calcium oxalate stone formers. Male rats were assigned to one of the following groups: (1) 1,25-dihydroxycholecalciferol (DHCC) (n = 8), (2) 1,25-DHCC + calcium antagonist Goe 6070 (a new 1,4-dihydronaphthyridine, Goedecke, Berlin) (n = 8), or (3) control (n = 8). 1,25-DHCC was administered for 6 days (120 pmol/24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A recent study of calcification in mice deficient in osteopontin (OPN) and/or Tamm-Horsfall protein (THP) showed that 10% of the mice lacking OPN and 14.3% of the mice lacking THP spontaneously form interstitial deposits of CaP within the renal papillae (20). Experimental induction of hypercalciuria in rats by administration of vitamin D also resulted in the intratubular deposition of CaP (24). Similarly, weanling rats given AIN-76 diet became hypercalciuric and produced intratubular concretions of CaP (13).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study of calcification in mice deficient in osteopontin (OPN) and/or Tamm-Horsfall protein (THP) showed that 10% of the mice lacking OPN and 14.3% of the mice lacking THP spontaneously form interstitial deposits of CaP within the renal papillae (20). Experimental induction of hypercalciuria in rats by administration of vitamin D also resulted in the intratubular deposition of CaP (24). Similarly, weanling rats given AIN-76 diet became hypercalciuric and produced intratubular concretions of CaP (13).…”
Section: Discussionmentioning
confidence: 97%
“…100 Administration of 1,25-dihydroxycholecalciferol alone resulted in the formation of CaP concretions in the kidney. 101 Concretion formation was reduced by calcium antagonist 1,4 dihydronaphthyridine. Deposition of CaP resulted in impaired renal function.…”
Section: Animal Model Studiesmentioning
confidence: 99%
“…Some patients with this disorder have lower levels of PTH in the absence of changes in 1␣,25(OH) 2 vitamin D 3 (4), whereas, other forms of normocalcemic hypercalciuria in humans may involve disordered regulation of 1␣,25(OH) 2 vitamin D 3 (3). In some cases, hypercalciuria may lead to kidney stone formation (16,18,38). Our results predict that patients with idiopathic hypercalciuria associated with lower levels of PTH may have reduced expression of ClC-5, which in turn would contribute to enhanced renal calcium excretion.…”
Section: Discussionmentioning
confidence: 99%